Analisis Preventive Maintenance Control Thermostat AC dan FCU untuk Pendingin Udara di Kamar Hotel - Iwan Setiawan; Yulizan Rizki (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2026)
This study analyzes the implementation of preventive maintenance on Schneider TC300 AC control thermostats and Fan Coil Units (FCU) in 488 rooms at the Fairmont Hotel Jakarta. The main problem addressed is the high number of guest complaints regarding non-cooling air conditioners, with initial data recording approximately 300 problematic rooms, 200 thermostat errors, and 100 damaged FCU units. The research method employs a descriptive quantitative case study approach through observation, interviews, documentation, and literature review. The findings show that preventive maintenance in the form of inspection, parameter adjustment, temperature calibration, and minor repairs successfully reduced guest complaints to 10 rooms, thermostat errors to 5 units, and problematic FCUs to 5 units.